Intestinal Microbiota and Serum Metabolic Profile Responded to Two Nutritional Different Diets in Mice - Wu, Zhifeng; Cheng, Wei; Wang, Zhenyu; Feng, Shuaifei; Zou, Huicong; Tan, Xiang; Yang, Yapeng; Wang, Yuqing; Zhang, Hang; Dong, Miaomiao; Xiao, Yingping; Tao, Shiyu; et al. (Frontiers in Nutrition, 2022)
There is an interaction and bidirectional selection between dietary intake and gut microbiota due to the different efficiency of nutrients in the gut. The nutritional composition of germ-free (GF) diets differs significantly from specific pathogen-free (SPF) diets. There is, however, no data revealing how SPF animals from the same microbial background respond to them and if they affect the host. We examined the growth of SPF mice on the GF diet and found that it reduced body weight, intestinal length and intestinal morphology. Interestingly, the GF diet increased the level of pro-inflammatory bacteria in the gut of SPF mice, including Proteobacteria, Burkholderiaceae, Alloprevotella and Parasutterella. Furthermore, GF diets caused significant increases in malondialdehyde (MDA), IL-1β, IL-6, and D-lactate levels in the serum of SPF mice and significantly altered their serum metabolic profile, especially amino acid metabolism. In conclusion, GF diets are not suitable for the growth and development of SPF mice. These findings, based on the role of gut microbiota in diet selection, provide new insights into the scientific and rational use of experimental animal diets.